Dakwah Mediasi: Perspektif Sejarah Islam - M Yakub (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2017)
This review discusses mediation as part of dakwah media. The purpose of this study is to analyze the role of mediation dakwah in overcoming various problems of the ummah. Using the historical analysis approach, this study tries to explore how the role of mediation dakwah in overcoming the conflicts that occur as part of the problems of the ummah. Dakwah is a way in the way to spread the teachings of Islam, with Islamic dakwah can be felt until the world. But in the process of dakwah sometimes encounter frequent clashes and obstacles, one of them in handling horizontal conflict and vertical conflict amid society, from ideology problem, understanding and even mutual thinking. This is where the need for mediation in the world of dakwah. We need to understand mediation to mediate or dispute resolution through mediate called mediators. For that mediation system, look for problem solving through mediator. The explanation of mediation is one of conflict resolution alternatives as a breakthrough on traditional settlement methods through litigation.